“Remember Me to Friends If I Have Any”: The Patriot War Letters of W.W. Dodge to Dr. Charles Osgood - Beasecker, Robert (Ontario History)

(untitled) (The Ontario Historical Society, 2023)
Colonel W.W. Dodge, an American citizen in the Canadian Rebellion.was among the crew of a schooner captured by Canadian militia off Fort Malden on the Detroit River. He was wounded, imprisoned at Fort Malden, Toronto and Quebec in succession, and made a daring escape from the latter location with Dr. Edward A. Theller. One or two of his letters, written while incarcerated in Canada, were published in a few newspapers at the time, but now new letters have been found. These documents, which are presented here, enhance our understanding of the Patriot War.